Slow Avalanche: Internationalizing the Renminbi and Liberalizing China’s Capital Account - Chang, Terry E. (Columbia Journal of Asian Law, 2012)
China finds itself in the unprecedented situation of internationalizing its currency while liberalizing its partially-closed capital account. This article discusses the steps, the risks and the predictions of such an unusual process. Steps: In its quest for capital account liberalization, China has adopted a four- pronged approach: (i) relaxing restrictions on inbound and outbound foreign direct investment, (2) expanding RMB trade settlement, (3) allowing the proliferation of RMB-denominated offshore financial products in Hong Kong (such as “dim sum” bonds), and (4) permitting new methods of repatriating offshore RMB for onshore investment (such as the RQFII scheme). Risks: Certain hazards still lie ahead in the liberalization process, including issues related to: liquidity and currency risk, concentration of credit risk, “hot money” and illegal funds, the complexity of interactions for multiple offshore RMB hubs, and asymmetry in currency demand accelerating the accumulation of foreign exchange reserves. Predictions: The Mainland government will likely seek to expand the use of the RMB specifically within the Asian region, among its fellow BRICS countries, as well as to the financial capitals in the West. Yuan appreciation will occur hand in hand with a slow metamorphosis from an export-driven economy to a consumer-driven model. Gradually, foreign countries will be encouraged to hold more yuan in their foreign reserves as their confidence in China’s financial and banking systems is improved through the development of a deposit insurance system and greater transparency as to legal protections available to them, and as more long term fixed-income financial products denominated in RMB for foreign investors are introduced.